2020
DOI: 10.1029/2020gl089311
|View full text |Cite
|
Sign up to set email alerts
|

Interannual Variability of Lower Equatorial Intermediate Current Response to ENSO in the Western Pacific

Abstract: The ocean currents of the tropical Pacific Ocean vary with El Niño‐Southern Oscillation (ENSO) cycles. A mooring time series obtained during 2014–2018 in the western Pacific reveal that interannual variability extends to Lower Equatorial Intermediate Current (LEIC). The LEIC velocity anomalies are significantly correlated with the Niño‐3.4 index at an 11‐month lag. Monthly velocity data from the global ocean physical reanalysis product and from a linear continuously stratified ocean model during 1993–2018 capt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 40 publications
3
13
0
Order By: Relevance
“…Our companion paper (Ma et al, 2020) found that the interannual anomaly of LEIC velocity at 142°E is mainly related to the second baroclinic mode of Rossby waves triggered by wind anomalies during the El Niño-Southern Oscillation (ENSO) mature stage. When the variability anomalies at seasonal, interannual, and intraseasonal time scales were larger than the mean currents on which they superimposed, the disappearance of the LEIC was observed at different longitudes (Cravatte et al, 2017;Firing et al, 1998;Ma et al, 2020;Marin et al, 2010). The seasonal variation of NGCUC-I is inversely correlated with that of the LEIC (Kawabe et al, 2008;Zenk et al, 2005).…”
Section: Research Lettermentioning
confidence: 86%
See 1 more Smart Citation
“…Our companion paper (Ma et al, 2020) found that the interannual anomaly of LEIC velocity at 142°E is mainly related to the second baroclinic mode of Rossby waves triggered by wind anomalies during the El Niño-Southern Oscillation (ENSO) mature stage. When the variability anomalies at seasonal, interannual, and intraseasonal time scales were larger than the mean currents on which they superimposed, the disappearance of the LEIC was observed at different longitudes (Cravatte et al, 2017;Firing et al, 1998;Ma et al, 2020;Marin et al, 2010). The seasonal variation of NGCUC-I is inversely correlated with that of the LEIC (Kawabe et al, 2008;Zenk et al, 2005).…”
Section: Research Lettermentioning
confidence: 86%
“…The seasonal variability in the LEIC (denoting both EIC and LEIC for convenience hereafter) velocity and temperature is induced by the vertical propagation of the first meridional Rossby wave, which is directly forced by the westward-propagating seasonal zonal wind fields (Kessler & McCreary, 1993;Marin et al, 2010). Our companion paper (Ma et al, 2020) found that the interannual anomaly of LEIC velocity at 142°E is mainly related to the second baroclinic mode of Rossby waves triggered by wind anomalies during the El Niño-Southern Oscillation (ENSO) mature stage. When the variability anomalies at seasonal, interannual, and intraseasonal time scales were larger than the mean currents on which they superimposed, the disappearance of the LEIC was observed at different longitudes (Cravatte et al, 2017;Firing et al, 1998;Ma et al, 2020;Marin et al, 2010).…”
Section: Research Lettermentioning
confidence: 86%
“…The westerly zonal wind stress anomaly ( τ x a ) in the above key regions during the mature stage of WPDO‐EN is more than twice as large as that of CPDO‐EN (Figure 4a). The previous study has demonstrated that the wind forcing during the El Niño mature stage (from Lag = −4 to Lag = 4) plays a critical role in the presence of the eastward U a (Ma et al., 2020). Furthermore, the full longitudinal range of westerly τ x a during the El Niño mature stage in the warm PDO is displaced eastward approximately 15° compared to that in the cold PDO (Figures 4a–4e).…”
Section: Resultsmentioning
confidence: 99%
“…Several works about the ENSO's impact on the equatorial intermediate currents (EICs) in the western Pacific have been done in recent years (e.g., Ma et al., 2020; J. Wang et al., 2021). The EICs here are defined as the zonal currents at the depths of 400–1,000 m. Three intermediate currents are located between 2°S and 2°N: the westward mean Equatorial Intermediate Current (EIC) at the depths of approximately 400–600 m, the westward mean Lower Equatorial Intermediate Current (LEIC) at the depths below approximately 800 m, and the eastward mean zonal current between the EIC and the LEIC (e.g., Cravatte et al., 2017; Firing et al., 1998; Johnson et al., 2002; Marin et al., 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation